A Juridical Analysis of the Overlapping Authorities of the Audit Board of Indonesia (BPK) and the Finance and Development Supervisory Agency (BPKP) in Auditing State Finances (An Analysis of Supreme Court Decision No. 886 K/Pid.Sus/2019) - Suanro Maruli T.R Samosir; Affila Affila; Suria Ningsih (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This thesis examines the juridical analysis of overlapping authority between the Audit Board of the Republic of Indonesia (Badan Pemeriksa Keuangan/BPK) and the Finance and Development Supervisory Agency (Badan Pengawas Keuangan dan Pembangunan/BPKP) in conducting state financial audits, with particular reference to Supreme Court Decision Number 886 K/Pid.Sus/2019. The study is motivated by the existence of dual audit results issued by BPK and BPKP concerning the same audit object, which resulted in significantly different calculations of state financial losses and raised issues of legal uncertainty in corruption law enforcement. This research employs a normative juridical method with statutory, conceptual, and case approaches. Primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, laws and regulations governing state financial audits, presidential regulations concerning BPKP, and relevant judicial decisions, particularly the Supreme Court ruling under study. Secondary legal materials include legal doctrines, scholarly writings, and journal articles. Data are analyzed qualitatively using deductive legal reasoning. he findings reveal that constitutionally and statutorily, BPK holds exclusive authority as the external auditor responsible for examining the management and accountability of state finances, including determining state financial losses. Meanwhile, BPKP functions as an internal government supervisory body whose authority is derived from presidential delegation within the executive branch. The overlap in audit practices between BPK and BPKP, as demonstrated in Supreme Court Decision Number 886 K/Pid.Sus/2019, reflects normative ambiguity and weak oordination mechanisms, leading to inconsistencies in audit outcomes and potential violations of legal certainty principles. his study concludes that the overlapping authority between BPK and BPKP in state financial audits necessitates clearer normative boundaries and harmonization of regulations to ensure legal certainty, prevent duplication of audits, and strengthen the credibility of state financial accountability and corruption law enforcement in Indonesia.